KAJIAN KINERJA OPERASI DAN PEMELIHARAAN JARINGAN IRIGASI STUDI KASUS DAERAH IRIGASI COKROBEDOG PROVINSI DAERAH ISTIMEWA YOGYAKARTA - , Ahmad Sofyan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The 194.17 ha of Cokrobedog irrigation area is a cross-regency irrigation area that lays between the Regency of Sleman and Bantul, where the tertiary irrigation area has been handed over to the water user farmer associations (P3A). They are P3A Rukun Makmur, P3A Rukun Sejahtera and GP3A Makmur Sejahtera as P3A Rukun Makmur and P3A Rukun Sejahtera alliance. Initially, the handing over of the irrigation management to P3As was not well responded due to the heavy tasks and responsibility endosed. Having various limitations, such as the irrigation knowledge, governmental budget, competency of the irrigation observation officer, as well as paddy-field functional changing, the performance of operational and maintenance of the irrigation network maintained by P3A/GP3A requires evaluation. The P3A institution performance was analyzed by using the SWOT method and P3A/GP3A institution was analyzed by using the AHP method. The performance of operational and maintenance of the Cokrobedog irrigation network was in best management by GP3A Makmur Sejahtera, and followed by P3A Rukun Sejahtera and P3A Rukun Makmur. The P3A institutional performance in conducting the operational and maintenance activity was quite active. Irrigation network renovation was carried out spontaneously in mutual-cooperaton enthusiasm. This was effective in preventing the irrigation network function from declining. The empowerment of P3A/GP3A was focused in the enhancement of the irrigation operational and maintenance, human resources quality and irrigation network reliability to ensure punctuality in time, amount and quality.